Analyzing mathematics formative test questions for higher-order thinking skills utilizing the Rasch model - Avrinda, Clarisa Aurelia; Slazenny, Amelline; Ghani, Fahad Abdul (Universitas Muhammadiyah Malang, 2024)
In the present day, education is anticipated to cultivate individuals who possess the 4C competencies, which encompass creative thinking, critical thinking and problem-solving, communication, and teamwork. In the 21st century, education is of growing significance in equipping students with learning aptitude, creativity, and proficiency in using technology and information media, enabling them to thrive and adapt. This research aims to examine and explain the attributes of questions that assess higher-order thinking skills using the Rasch Item Response Theory (IRT) method. This study is a Descriptive quantitative research. This study focused on analyzing the response patterns of 70 class XI students from SMA Negeri 3 Tuban towards a formative test instrument that consisted of five answer choices. The test set is derived from the execution of formative assessments. The Rasch model was utilized for data analysis with the assistance of ConQuest. The analysis results indicate that all items conform to the Rasch model. Based on the difficulty level, 15% of the items fell into the troublesome category, while 85% were classified as moderate. The difficulty level values go from -1,094 to 1,250.